Royal Funerary Equipment of a King Sobekhotep at South Abydos: Evidence for the Tombs of Sobekhotep IV and Neferhotep I? - Wegner, Josef.
Recent excavations at South Abydos have produced evidence for the date and ownership of a group of royal tombs adjacent to the tomb enclosure of Senwosret III. Tombs S9 and S10, two structures investigated initially by Arthur Weigall, are late Middle Kingdom royal tombs constructed using the distinctive format of the late Middle Kingdom royal pyramid interiors known primarily from the Memphite region. Excavations during 2013–2015 in and around tomb S10 now permit its attribution to one of the Thirteenth Dynasty Sobekhotep kings. Evidence includes a monumental funerary stela bearing the nomen Sobekhotep that appears to derive from a now-destroyed chapel associated with S10. The stela was likely reused in an adjacent intrusive tomb: that of the Second Intermediate period king, Woseribre-Senebkay. In Senebkay’s tomb, excavation revealed that king’s canopic chest, constructed from reused planks that had originally belonged to the cofn of a king Sobekhotep. The original painted texts include a distinctive set of Cofn Texts (Spells 777–785), examples of which date to the middle–late Thirteenth Dynasty. The probable chronological range of these spells, paired with additional lines of evidence suggest that S10 is the burial place of one of the longer-reigning Sobekhotep kings of the middle Thirteenth Dynasty, likely Sobekhotep IV. The proximity of S10 to the similarly designed tomb S9 implies royal burials at South Abydos of two closely connected kings, the brother kings Neferhotep I and Sobekhotep IV, who were unusually active at Abydos and may have chosen to associate their tombs with the mortuary complex of Senwosret III. During the later Second Intermediate period, Senebkay (ca. 1650–1600 BCE) and associated kings reused both funerary equipment and materials from these late Middle Kingdom tombs.